Efficient mixed-cation perovskite photovoltaic cells via additive-assisted slot-die deposition. (May 2022) - Lee, Hyun-Jung; Na, Seok-In
Highlights: 2-hydroxyethyl acrylate (HEA) was introduced as a functional additive to improve slot-die-processed perovskite. HEA helps the crystal growth of perovskite. HEA passivates the defects at the perovskite surface. HEA based PeSCs show good stability, maintaining an initials efficiency of 80% under air for 95 days. Abstract: The main objective of this study was to enhance the quality of slot-die-processed perovskite film layer using an additive process that could improve the performance and stability of perovskite devices. To improve slot-die-processed perovskite, 2-hydroxyethyl acrylate (HEA) additive with -OH was utilized as an effective functional group. The addition of HEA controlled the perovskite's growth, enlarged perovskite's grain size, and reduced perovskite's defects. As a result, the slot-die-processed device fabricated with HEA as additive produced a high efficiency of 16.08% and a good stability, maintaining an initial efficiency of 80% under air for 95 days. Graphical abstract: Image, graphical abstract